Studies of true bugs of Xinjiang, western China. I. Leptopodomorpha: shore bugs (Hemiptera: Heteroptera: Saldidae) - Vinokurov, Nikolai N.; Luo, Zhaohui; Lü, Zhaozhi (Zootaxa, 2012)
The family Saldidae in Xinjiang (Western China) includes 19 species belonging to five genera from the subfamilies Chiloxan-thinae (1 sp.) and Saldinae (18 spp.). A new species, Halosalda minuta Vinokurov, Luo & Lü, sp. n., is described from the east-ern part of the Tarim depression. The new species differs from congeners by the small body size, relatively large head, longerantennal segment 2, and structures of male genitalia. S. sibiricola Cobben, 1985 is recorded as new for China, and three speciesare new to the fauna of Xinjiang: Saldula orthochila (Fieber, 1859), S. pallipes (Fabricius, 1794), and Salda littoralis (Linnaeus, 1758). Halosalda lateralis (Fallén, 1807) is reported for Kyrgyzstan for the first time.